A new approach to the ecotourism potential of Yusufeli district within the framework of AHP-SWOT - İnci Zeynep Yılmaz; Ufuk Demirci (Turkish Journal of Forestry)
In this study, it is aimed to determine what can be realized in the scope of ecotourism in Yusufeli district of Artvin, which has moved to a new settlement. For this purpose, A'WOT analysis, in which SWOT analysis and AHP method are used together, was used in the study. In this context, firstly, a SWOT matrix was formed with the support of the relevant literature. In order to determine the degree of importance of the matrix factors, the AHP method was used and the opinions of local tour agencies, academicians, NGOs, local administrators in the region and managers at the Yusufeli Forest Management Directorate who live in Yusufeli district or have information about Yusufeli district were obtained. According to the results of the study, while the strengths of Yusufeli district are the presence of places with magnificent natural beauty, the presence of places that will serve the belief and cultural heritage with historical importance and the presence of places based on river tourism (rafting, canoeing, boat tours, etc.) (33.3%); the weakest aspect is lack of activities for activities such as accommodation, pensions, restaurants, tour trips, etc. due to the relocation to a new settlement and the lack of related promotions (59.4%). In addition, the fact that Yusufeli district allows different ecotourism activities (41.3%) is seen as the biggest opportunity, while the relocation of the old Yusufeli district to another place due to dam construction (41.3%) is seen as the biggest threat.